(E)-3-(2,5-Difluorophenyl)-1-phenylprop-2-en-1-one - Leonardo Santos de Barros; Maria Clara Ramalho Freitas; Vinícius Rangel Campos; Francisco Assis da Silva; José Carlos Netto-Ferreira; Darí Cesarin-Sobrinho (IUCrData, 2016)
The title chalcone derivative, C15H10F2O, is almost planar, with the benzene ring being inclined to the phenyl ring by 7.45 (9)°. The conformation about the C=C bond is E. In the crystal, molecules are linked by two pairs of C—H...F hydrogen bonds, forming inversion dimers enclosing R22(8) and R21(10) ring motifs. The dimers stack along the a axis with the separation of the C=C bonds being 4.2926 (4) Å.